Optimizing Infrastructure planning for Effective Supply ChainManagement - Tekade, Atul; Rangari, Amol D. (Journal of Neonatal Surgery, 2025)
Efficient logistics and supply chain management are essential for ensuring smooth business operations and maintaining competitiveness. This research examines the role of infrastructure planning and supply management in optimizing logistics networks. Proper infrastructure development enhances transportation efficiency, minimizes delays, and reduces operational costs. Additionally, effective supply management ensures the availability of raw materials, streamlines inventory control, and improves demand forecasting. The study explores key strategies, challenges, and technological advancements in logistics operations, highlighting their impact on overall business performance. With the growing complexity of global supply chains, companies must integrate innovative solutions to enhance efficiency and resilience. By implementing well-structured infrastructure and supply chain strategies, businesses can improve service quality, reduce risks, and achieve long-term sustainability in an increasingly dynamic market